Granulocyte colony-stimulating factor promotes regeneration of severed facial nerve in rats - Fujimaki, Yoko; Kondo, Kenji; Nishijima, Hironobu; Kikuta, Shu; Yamasoba, Tatsuya (Frontiers in Neuroscience, 2024)
Background and aimThe administration of growth and neurotrophic factors has been attempted experimentally as a new therapeutic strategy for severe facial paralysis. Granulocyte colony-stimulating factor (G-CSF) has an effect on the treatment of central nervous system injuries, such as cerebral infarction and spinal cord injury. This study aimed at examining the effects of G-CSF on facial nerve regeneration in rats.MethodsThe left facial nerve of rats was either partially resected (resection group) or severed and sutured (suture group) at the main trunk outside the temporal bone. In each surgical group, saline or G-CSF was administered via the gelatin hydrogel drug delivery system. The suture group was further divided into two subgroups for the late administration of G-CSF (2 weeks after surgical treatment) or immediate administration of G-CSF after surgical treatment. Recovery of the facial nerve was assessed by the evaluation of facial movements (after 12 weeks), complex muscle action potential amplitude measurements (after 2, 4, 8, and 12 weeks), electroneurography values (after 12 weeks), and histological evaluation (comparison of myelinated axon diameters among the groups).ResultsRecovery of the function and morphology of damaged nerves was faster in the suture groups than in the resection group. In the suture groups, recovery was faster for G-CSF-treated rats than for saline-treated rats. Furthermore, recovery was faster in the group that received G-CSF immediately after surgical treatment than in the group that received G-CSF 2 weeks later. However, the group that received G-CSF 2 weeks later also showed faster recovery than did the control group.ConclusionG-CSF effectively promoted nerve regeneration during facial nerve paralysis. Thus, G-CSF may be a potential treatment strategy for injured facial nerves as it has been safely administered in clinical treatments for hematological diseases.